Teoria e Práxis Revolucionária dos Trotskistas Brasileiros (São Paulo, 1930-1945) - Alzira Lobo de Arruda Campos; Marília Gomes Ghizzi Godoy; Rafael Lopes de Souza (Historia Crítica, 2019)
It is possible to verify the role performed by the first activist dissidents from Stalinism aiming at noticing the impact from Marxist-Leninist theory and Russian Revolution on the organization of thinking and left-wing militancy in the capital of São Paulo. The Brazilian Trotskyists ideas and action, during the 1920s and 1930s, are re-evaluated from the analysis of primary sources, in order to understand the interpretations that the dissidents have given to historical events in which they were active and fervent protagonists. In that manner, we expect to get to a more rigorous interpretation of the formation and development of PCB (Brazilian Communist Party). Originality: The studies on PCB usually assume a Stalinist bias, despising Trotskyists as cowards or traitors of Proletarian Revolution. This analysis reveals the Trotskyists interpretation of the events in which they participated, with the support of vast documentation, mostly unpublished, preserved in workers and police archives. Methodology: This approach uses concepts consecrated by the Marxist-Leninist dialectical method, raised to the category of “subject knowledge”, understood as blocks of historical knowledge that were present and disguised in the interior of functional and systematic sets, and that were disqualified as non-conceptual knowledge, hierarchically inferior. This is an approach that questions the formal systematizations from consecrated authors and raises the narratives of individuals who were silenced by power. By focusing on human actions and meanings that go unnoticed in broad analytical frameworks, the goal is to extract from facts that are apparently common a relevant sociocultural dimension, with the use of the narrative as a resource. Conclusions: Strongly influenced by immigrants and by anarchism, the Brazilian labor movements created their own labor unions and parties, and the most important was the Brazilian Communist Party, founded in 1922. In no time, as a consequence of the mortal fight between Stalin and Trotsky, the Brazilian comrades strongly disagreed about the course of the revolution, originating a severe dispute for the dominance of the party’s direction, considering that it was moving away from historical materialism and condemned, for this procedure, the proletarian progress to deviance and defeat. The opponent most operating group, gathered in the International Communist League, started a constant fight against the party’s direction and political policy, becoming the repression preferential victims during the difficult times under the dictatorship of Getúlio Vargas.